p16 - a possible surrogate marker for high-risk human papillomaviruses in oral cancer? - Thanun Sritippho (2018)
Background: High-risk human papillomaviruses (HR-HPV), particularly types 16 and 18, have been found to play an important role in head and neck cancer, including oropharyngeal squamous cell carcinoma (OPSCC) and oral squamous cell carcinoma (OSCC). p16, a cell cycle inhibitor, has been postulated as a surrogate marker for HR-HPV, since p16 is aberrantly overexpressed in such lesions, especially in HR-HPV-positive OPSCC. However, p16 as a surrogate marker for HR-HPV infection in cancers of the oral cavity remains controversial. Objective: The objectives of the study were to investigate the expression of p16 and the presence of HR-HPV in OSCC and oral verrucous carcinoma (VC) and to determine if p16 could be used as a surrogate marker for HR-HPV. Materials and Methods: Forty one formalin-fixed, paraffin-embedded tissues of OSCC (n=37) or VC (n=4) with clinical and histopathologic data of each case were collected. Expression of p16 was determined by immunohistochemistry, focusing on both staining intensity and numbers of positive cells. The presence of HPV types 16 and 18 was detected by polymerase chain reaction (PCR). Descriptive statistics were employed to describe the demographic, clinical, and histopathologic parameters. Associations between p16 overexpression, HR-HPV and all variables were determined by Fisher's exact test, odds ratios (ORs) and corresponding 95% confidence intervals (CIs). In addition, the use of p16 as a surrogate marker for HR-HPV was analyzed by sensitivity and specificity tests. Results: p16 was overexpressed in 8/37 cases (21.6%) of OSCC and 2/4 cases (50%) of VC. HPV-16 was detected in 4/34 OSCC cases (11.8%) and HPV-18 was detected in 1/34 OSCC cases (2.9%). Co-infection of HPV-16/18 was detected in 1/4 VC cases (25%). Both p16 overexpression and HR-HPV were significantly associated with young patients with both OSCC and VC (p < 0.05, OR 20, 95% CI 1.9-211.8; p < 0.05, OR 23.3, 95% CI 2.4-229.7, respectively). p16 was able to predict the presence of HPV-16/18 in OSCC with 40% sensitivity and 79.3% specificity and in VC with 100% sensitivity and 66.7% specificity, respectively. Conclusions: p16 overexpression was found in 24.4% of both OSCC and VC. HR-HPV, regardless of type, was detected in 15.8% in cases of OSCC and VC combined. The results of sensitivity and specificity tests suggest that p16 can be used as a surrogate marker for HR-HPV in OSCC and VC.